Study on food habits of herring (Clupea fimbriata) in Ujung Pangkah Waters, East Java - . Sulistiono; M. Robiyanto; M. Brodjo; C.P. Simanjuntak (Jurnal Akuakultur Indonesia)
Herring Clupea fibriata is an important fishery resource in Indonesia. This species is found in large number in Ujung Pangkah Waters. This study aims to investigate food habits of the species. The study was done from July to December 2005, in Ujung Pangkah Waters (Gresik, East Java Province), using samples of 313 individuals consisting of 147 males and 166 female fish, collected by gill net and fix net. Study result shows that food habit of the herring was consisted of Bacillariophyceae (7 genera), Crustacea (3 genera), Ciliate (2 genera), Dynophycea (2 genera), and detritus. Bacillariophyceae is a main food, Crustacea is additional food, and Ciliata and detritus is complementary food both for male and female fish. Electivity indeks of the fish varied from -0,99 to 0,45 (male) and -0,98 to 0,51 (female). According to the index, Skeletonema and Calanus are the dominant food of the fish collected in the Ujung Pangkah Waters.